Intravitreal anti-vascular endothelial growth factor therapy in the treatment of vision loss associated with hematologic malignancy - Thomas P. Toohey; Jake Shortt; Nevin John; Salmaan Al-Qureshi; Sanjeewa S. Wickremasinghe (American Journal of Ophthalmology Case Reports)
Purpose: To determine the effectiveness of anti-vascular endothelial growth factor (VEGF) therapy in the setting of optic disc edema secondary to hematologic malignancies. Observations: The report features two patients (one male, one female) in their 70's with biopsy proven hematologic malignancies who subsequently developed optic disc edema. The patients were commenced on a trial of successive intravitreal Aflibercept 2mg/0.05mL therapy. The best corrected visual acuity for patient 1 improved from 20/50 oculus dexter (OD) and 20/80 oculus sinister (OS), to 20/20 OD (4 lines Early Treatment of Diabetic Retinopathy Study (ETDRS)) and 20/32 OS (4 lines ETDRS). Similarly, patient 2's best corrected visual acuity improved from 20/100 OU to 20/50 OD (3 lines ETDRS) and 20/40 OS (4 lines ETDRS) following initiation of treatment. In addition, optical coherence tomography imaging obtained before and after therapy demonstrated an improvement in both patient's optic disc edema and cystoid macular edema. Conclusions and importance: The findings of this report suggest that in patients with a known hematologic malignancy, optic disc edema and cystoid macular edema may be amenable to anti-VEGF treatment, especially if there are clinical and angiographic features of vascular endothelial growth factor overexpression.